P77 Colposcopy of cervical warts. (23rd May 2012) - Evans, J; Toeima, E; Elsawy, M
Abstract : Background: BASHH guidelines for the management of genital warts do not recommend colposcopy for women with cervical warts unless there is diagnostic uncertainty or clinical concern. Our local cervical cytology guidelines advise colposcopy regardless of cervical cytology result. Aim: To review the colposcopic outcome of women referred from our genitourinary medicine department because of cervical warts. Method: Retrospective case note review of women referred for colposcopy because of cervical warts from December 2005 to November 2010. Results: 25 women with cervical warts underwent colposcopy. The median age was 22 years (range 17–52 years). Four of the 25 were found to have a normal cervix at the time of colposcopy. 21 of 25 had persistent cervical warts, three consistent with benign human papilloma virus (HPV) infection and in whom no further action was taken. 18 of 21 with persistent cervical warts underwent biopsy. Histological results indicated 10 had HPV only, six had CIN 1, one had CIN 2, and one had normal histology. The woman with CIN 2 and one with CIN 1 had a complete LLETZ excision of the lesion. All women with CIN were under 25 years old. Conclusion: A third of the women biopsied had CIN, however only one had a high grade abnormality. No invasive cancers were found. Conservative management for young women with CIN 2 is acceptable in current colposcopic practice. Our study indicates unscheduled screening or referral to colposcopy is unrewarding.